Comparative study of laparoscopic ovarian drilling and medical treatment in polycystic ovarian disease - Verma, Hema; Srivastava, Prachi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To evaluate the result after medical treatment and laparoscopic ovarian drilling in PCOS patients and to compare the results of these two methods. Methods: In this prospective study 50 women with polycystic ovarian disease, were divided into two group,25 women received medical treatment and 25 women received surgical (laparoscopic ovarian drilling) treatment. Effect of treatment on ovulation, menstruation, fertility and androgen level was determined 3 month after therapy. Results: There was significant increase in ovulation and fertility, decrease in androgen levels and decrease in LH/FSH in individual groups when compared with pretreatment levels but difference between groups A and B was not statistically significant for these parameters. Conclusions: Medical treatment and laparoscopic ovarian drilling are equally effective in treating the women of polycystic ovarian disease. Result of both the treatment are similar in this study. However medical treatment should be the first line therapy, it has significant benefit for use in OPD, low cost, no hospital stays and convenience to the patient.